Metal Chelates of Hydrazo-Dimedone Dyes. Chelating Tendencies of 5,5-Dimethylcyclohexane-2-(2-Hydroxo-4- Methylphenyl) Hydrazono 1,3 Dione with Samarium(III), Lutetium(III) and Dioxouranium(II) - A. T. Ramadan, Atef (Asian Journal of Chemistry, 2010)
The stability constant of 5,5-dimethylcyclohexane-2-(2-hydroxo-4-methylphenyl) hydrazone-1,3-dione (DC-4-Me-PHD) complexes with Sm(III), Lu(III) and UO2(II) in 50% (v/v) isopropanol-water solvent at 30ºC have been investigated by pH-metry and spectrophotometric methods. Probable structures of the metal chelates are inferred from electronic absorption spectra, conductivity measurements and infrared examination of the solid complexes. The use of DC-4-Me-PHD as an analytical reagent for the spectrophotometric determination of samarium, lutetium and uranium ions has also been discussed.